Pengujian Pola Siklus Arus Kas dalam Memprediksi Kebangkrutan - Eddy Suranta; Pratana Puspa Midiastuty; Rini Indriani; Anton Robiansyah (Jurnal Akuntansi, 2021)
Abstract The pattern of cash flow from operating, investing, and financing activities of each company is one of the important information for many parties, especially in predicting company performance and the probability of bankruptcy. The cash flow pattern used in this study uses 8 forms of cash flow patterns. The data collected consisted of 96 companies listed on the Indonesia Stock Exchange with an observation period of 2010 to 2019. The purpose of this study was to determine whether there are differences in any cash flow patterns between companies that went bankrupt and those that did not. This study further aims to prove the cash flow patterns of operating, investing, and financing activities can be used to predict the probability of bankruptcy. The results prove that there are significant differences in cash flow patterns between companies that have gone bankrupt and those that are not. The results of further research prove that the company has the greatest probability of bankruptcy when the company has negative operating cash flows, positive cash flows from investing activities and positive cash flows from financing activities. Furthermore, the company experiences the probability of bankruptcy when the company has negative operating and investing cash flows with positive cash flows from financing activities. The company does not have a probability of bankruptcy when the company has positive operating cash flow with negative investment cash flow and positive cash flow from financing activities. Keywords: Bankruptcy, Cash Flow Pattern, Cash Flow from Operating, Cash Flow from Investing, and Cash Flow from Financing